Pengaruh Protabilitas dan Likuiditas terhadap Harga Saham pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Dimediasi oleh Persistensi Laba Sebagai Variabel Intervening - Shaleh, Muthmainnah M. (Jayapangus Press, 2024)
Financial performance determines the company's current share price. The better the company's financial performance, the better the company's share price and vice versa. This research discusses the influence of profitability and liquidity on stock prices which is mediated by profit persistence as an intervening variable. Profitability and liquidity are part of financial performance. The research method used is a quantitative approach. The data used are the financial reports of manufacturing companies listed on the Indonesia Stock Exchange for 2016-2020, totaling 134 companies. Data collection is carried out via the link www.idx.co.id. The data analysis used is Eviews 10 to test direct variable relationships and the Sobel Test to test indirect variable relationships. The results of research show a probability value of >0.05, which means that profitability and liquidity have an effect on share prices, as well as profitability and liquidity have an effect on profit persistence. Meanwhile, the Sobel test shows that the Sobel test value obtained a Return On Assets (ROA) value of -0.160, Return On Equity (ROE) of -0.03260, Earning Per Share (EPS) of -0.2879 and Current Ratio (CR) of 0.0807, this value < 0.05, so even though it is mediated by earnings persistence, both have no effect on stock prices. Meanwhile, the Net Profit Margin is 0.2994, the gross profit margin is 0.3241, this value is > 0.05, meaning it has an effect on share prices mediated by profit persistence.